China’s CBM exploration and production and associated technological advancements: A review and reflections - Jianping YE (Meitian dizhi yu kantan)
Objective and Methods Based on extensive scientific and technical literature and technical data on coalbed methane (CBM) exploration and production projects, this study conducted a comparative analysis of the development process and latest advances in China’s critical technologies for CBM exploration and production and reviewed the CBM exploration and production history of this country over the past three decades. Accordingly, this study discussed the theoretical and technical challenges in CBM exploration and production and proposed future development directions. Advances The results indicate that the insights into conversion between adsorbed and free deep CBM prove to be a significant theoretical understanding. The breakthroughs in the ideological understanding of exploration and production, as well as the innovative applications of near-bit geosteering drilling technology and multistage volume fracturing technology for horizontal wells, elevate China’s deep CBM production to a higher level. Recent years have seen major advances in the accumulation mechanisms and modes of deep CBM, assessment methods for CBM exploration and production, and knowledge about CBM production regularity. The geology-engineering integration serves as an effective method for the prediction and assessment of play fairways, well deployment, and the research and development of adaptive technologies. Presently, the most advanced comprehensive technology system for CBM production consists of the deployment of cluster horizontal well groups, the deployment of horizontal well groups combined with vertical and directional well groups, the multistage volume fracturing of horizontal wells, and the intelligent dewatering and CBM production using rodless lifting. Furthermore, the efficient CBM production of thin coal seams suggests a breakthrough in the lower limit of coal seam thickness for CBM production and the discovery of new target layers for CBM production. China’s CBM production focuses primarily on CBM reservoirs dominated by adsorbed gas and those bearing both adsorbed and free gas. The two major CBM reservoir types differ significantly in gas accumulation mechanisms and the technologies and philosophies for CBM exploration and production. Prospects It is recommended that the future CBM exploration and production in China should center on four fields. Specifically, deep CBM will be the primary target for future CBM exploration and production and technological research, and it is necessary to intensify and accelerate the exploration and production of deep CBM resources in platform-type sedimentary basins such as the Ordos, Junggar, Turpan-Hami, Tarim, and Sichuan Basins. Large-scale production of moderately deep CBM is identified as an important direction. Shallow CBM, acting as the “ballast stone” for the development of the CBM industry, is supposed to keep continued stable production and serve as the replacement for current CBM resources. Additionally, CBM in low-rank coal reservoirs is a potential target for CBM exploration and production.